GROWTH OF ELEPHANT GRASS (Pennisetum purpureum) WITH GIVING LIQUID ORGANIC FERTILIZER (GOAT URINE AND FRUIT WASTE) - R. H., LESTARI; RAMADANI, D.; ., NURFAIDA; AMALIAH, D. D.; ., TAHYUL (Majalah Ilmiah Peternakan; Vol 27 No 3 (2024): Vol. 27 No. 3 (2024)DO - 10.24843/MIP.V27.i03.p05, 2024)
Liquid organik fertilizer is one of the most important ingredients in effot to safely improve soil fertility. Liquid organic fertilizer is one of the most important ingredients in an effort to safely improve soil fertility. The main ing- redients in the manufacture of liquid organic fertilizer (POC) are goat urine and fruit waste (noni, pineapple peel, tomato and kepok banana peel). Goat urine contains nutrients N, P and K which are good for plant growth. POC ap- plication can be applied to elephant grass (Pennisetum purpureum) which is a type of grass that is easy to find, easy to grow, and easy to breed in the tropics. The research aimed to look at growth of elephant grass with giving liquid organic fertilizer (goat urine dan fruit waste) on 60 day defoliaton. The research design applied was a completely randomized design (CRD) with 4 treatments giving fertilizer and 3 replicates. Treatment P0= control, P1=150ml/ plybag, P2= 300ml/polybag and P3= 450 ml/polybag. The variables observed were plant height, number of leaves and number of tillers. The results showed that the use liquid organic fertilizer on doses 450 ml/polybag gave the best results on variables measured in details of the best plant height 151.9 cm, number of tiller 6,6 pieces and the highst number of leaves at dose 300ml/polybag is 74,6 pieces.